From head shops to Whole Foods : the rise and fall of activist entrepreneurs - Davis, Joshua Clark (Columbia studies in the history of U.S. capitalism., 2017)
In the 1960s and '70s, a diverse range of storefronts-including head shops, African American bookstores, feminist businesses, and organic grocers-brought the work of the New Left, Black Power, feminism, environmentalism, and other social movements into the marketplace. Through shared ownership, limited growth, and workplace democracy, these "activist entrepreneurs" offered alternatives to conventional profit-driven corporate business models. By the middle of the 1970s, thousands of these enterprises operated across the United States-but only a handful survive today. Some, like Whole Foods Market, have abandoned their quest for collective political change in favor of maximizing profits. Vividly portraying the struggles, successes, and sacrifices made by these unlikely entrepreneurs, Clark Davis writes a new history of movements and capitalism by showing how activists embraced small businesses in a way few historians have considered. The book rethinks the widespread idea that the work of activism and political dissent is inherently antithetical to business and market activity. It uncovers the historical roots of contemporary interest in ethical consumption, social enterprise, mission-driven businesses, and buying local while also showing how today's companies have adopted the language-but not often the mission-of liberation and social change.